Long Term Follow-Up of Pediatric Mandibular Reconstruction With Human Transforming Growth Factor-β3. Issue 5 (July 2020) - Ferretti, Carlo; Ripamonti, Ugo
Abstract : Abstract: Translating bone regeneration induced by recombinant human bone morphogenetic proteins from animal models to human patients has proven inexplicably inconsistent. This prompted us to test in 5 pediatric patients, an alternative osteoinductive morphogen, recombinant human transforming growth factor β3 (hTGF-β3 ), to reconstruct mandibular defects of such a size to preclude reconstruction with autologous bone. An osteoinductive implant of human demineralized bone matrix (DBM) loaded with 125 μg hTGF-β3 per gram of DBM was implanted into one defect, and 250 μg hTGF-β3 per gram of DBM in another. Thereafter in 3 patients limited amounts of particulate cortico-cancellous bone graft harvested from the posterior iliac crest were combined with 250 μg hTGF-β3 per gram of DBM. Patients were followed up for 3 to 6 years. Three patients achieved clinically significant osteoinduction, 1 patient with hTGF-β3 only, and 2 by combining hTGF-β3 with a small supplement of autologous bone. One patient with hTGF-β3 only and followed up for 5 years retains a viable reconstruction but has had sub-optimal bone regeneration. One patient had osteoinductive failure due to sepsis although the plate reconstruction remains viable. Recombinant human TGF-β3 initiates osteoinduction in humans and potentiates autologous bone graft activity allowing the reconstruction of large mandibular defects in pediatric patients.